2010
DOI: 10.1073/pnas.0914492107
|View full text |Cite
|
Sign up to set email alerts
|

HUNK suppresses metastasis of basal type breast cancers by disrupting the interaction between PP2A and cofilin-1

Abstract: Metastasis leads to the death of most cancer patients, and basal breast cancer is the most aggressive breast tumor type. Metastasis involves a complex cell migration process dependent on cytoskeletal remodeling such that targeting such remodeling in tumor cells could be clinically beneficial. Here we show that Hormonally Upregulated Neu-associated Kinase (HUNK) is dramatically downregulated in tumor samples and cell lines derived from basal breast cancers. Reconstitution of HUNK expression in basal breast canc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
44
0
1

Year Published

2010
2010
2016
2016

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 38 publications
(50 citation statements)
references
References 32 publications
5
44
0
1
Order By: Relevance
“…In this regard, in contrast to our genetic and biochemical evidence for pro-tumorigenic effects of Hunk in HER2/neuinduced tumorigenesis and pro-metastatic effect of Hunk in cmyc-induced mammary tumorigenesis, it has recently been suggested by Mak and colleagues that Hunk might play an opposing role in basal-like human breast cancers, wherein Hunk overexpression may suppress metastatic potential (87). While the findings of that study are formally consistent with the possibility that the role of Hunk in metastasis may be cell type specific, it is important to note that their study focused primarily on in vitro systems in which Hunk was exogenously overexpressed in cell lines that do not otherwise express Hunk.…”
Section: Discussionmentioning
confidence: 40%
“…In this regard, in contrast to our genetic and biochemical evidence for pro-tumorigenic effects of Hunk in HER2/neuinduced tumorigenesis and pro-metastatic effect of Hunk in cmyc-induced mammary tumorigenesis, it has recently been suggested by Mak and colleagues that Hunk might play an opposing role in basal-like human breast cancers, wherein Hunk overexpression may suppress metastatic potential (87). While the findings of that study are formally consistent with the possibility that the role of Hunk in metastasis may be cell type specific, it is important to note that their study focused primarily on in vitro systems in which Hunk was exogenously overexpressed in cell lines that do not otherwise express Hunk.…”
Section: Discussionmentioning
confidence: 40%
“…This observation extends our previous finding that Hunk is required for the development of HER2/neu-induced mammary tumors (3), which exhibit a luminal epithelial phenotype, by demonstrating that Hunk is also required for the development of mammary tumors in Pten mutant mice, which display basal-like characteristics (22). This latter finding is of particular interest in light of a recent report proposing that Hunk functions as a suppressor of metastasis, based on experiments in basal-like human breast cancer cell lines (23). To extend their in vitro findings, these authors suggested that crossing Hunk −/− mice to mouse models for HER2/neu as well as basal-like breast cancers would yield information pertinent to human breast cancer.…”
Section: Discussionmentioning
confidence: 98%
“…In this case, we believe that the only way to ensure that the fi nal effect of CFL-1 is inhibition of its function, is direct targeting (or targeting through its main regulators LIMK or PP2A). We and others have demonstrated how the mutation of serine 3 to aspartic acid of CFL-1 (causing a conformational change similar to constitutive phosphorylation) exerts a clean cytoskeletal effect in tumour cells [116]. Whereas viability and replication remain unaltered, cancer cells are unable to grow on in adhesion-independent manner, migrate in vitro or produce metastasis in vivo [116].…”
Section: Cytoskeleton-targeting Drug Development Issuesmentioning
confidence: 97%
“…We and others have demonstrated how the mutation of serine 3 to aspartic acid of CFL-1 (causing a conformational change similar to constitutive phosphorylation) exerts a clean cytoskeletal effect in tumour cells [116]. Whereas viability and replication remain unaltered, cancer cells are unable to grow on in adhesion-independent manner, migrate in vitro or produce metastasis in vivo [116]. Drugs targeting upstream signalling molecules are justifi ed in the case of activating mutations (i.e., Pi3K, EGFR, etc.…”
Section: Cytoskeleton-targeting Drug Development Issuesmentioning
confidence: 98%